Adobe Premiere Pro complete course (Photocopy) - L. Baker Donna (American : Wiley, 2004)
All the files and materials you need to complete the video project
Bonus discussions on additional Premiere Pro features, methods of exporting, and special effects
Bonus session featuring tutorials that explain how you can create your own version of titles and graphics used in the project
CD-ROM Contents
From the Back Cover
Product Description
Seybold Seminars, Publications & Consulting is the leading brand helping graphic design and Web professionals understand and work with the latest digital technologies.
System Requirements: See the About the CD-ROM Appendix for details and complete system requirements.
Text provides a complete course showing how to master the full range of Premiere Pro tools and techniques while working on a single project. Includes twelve sessions and more than eighty step-by-step tutorials. For beginning to intermediate users. Softcover.
Tryout version of Adobe® Audition, demo versions of Borix FX and Boris CONTINUUM Complete, and a demo version of SpiceMASTER
Use effects and transitions to change the action from scene to scene.
Use multiple sequences to create complex nested effects.
Use the Title Designer to create sophisticated titles.
Written by a Premiere Pro expert and illustrated throughout in full color, this Complete Course shows you how to master the full range of Premiere Pro tools and techniques while working on a single project. Twelve sessions and more than eighty step-by-step tutorials, accompanied by vivid color images and screen shots, walk you through the creation of a ninety-second, professional- quality video from start to finish. After completing the course, you’ll have an impressive portfolio piece and a thorough understanding of Adobe Premiere Pro fundamentals.
Keywords: Digital video; Motion pictures